(untitled) (Damascus University Journal for engineering sciences, 2021)
In this paper 1/6 of VVER-1000 core with MOX fuel was modeled using MCNP5-beta for calculating the reactor effective multiplication factor in six operation cases. The fuel consists 70% of low enriched uranium (UO2) and 30% of MOX fuel (235U and 239Pu). Good agreements have been noticed between our calculation using MCNP5-beta code and another results which were calculated using the MCNP4C, MCU, and RADAR codes. The delayed neutron fraction, average neutron flux and the control rod worth for existing fuel (UO2) and new fuel (70% UO2 and 30% MOX) were calculated also in this paper.